Refined Dimension-Dependent Analysis for Private Convex Learning and Implications for Fine-Tuning - Li, Xuechen; Liu, Daogao; Hashimoto, Tatsunori; Inan, Huseyin; Kulkarni, Janardhan (Jana); Lee, YinTat; Thakurta, Abhradeep Guha (2022)
Abstract to come...